Electronic-voting approach with an open cloud computing architecture (International Journal of Engineering and Computer Science, 2014)
The concept of cloud computing has passed into every area and the academic lexicon in an ambiguous manner, as cloud dust is being sprinkled on an excess of emerging products. Discussing the complexity and protecting against the caprice of the moment, this paper exhibits the notion behind the hype of cloud computing and evaluates its relevance to electronic government and electronic voting information system. Adopting a cloud computing approach for electronic voting solutions is investigated, reviewing the architecture within the previously described context. Taking a further step ahead, this paper proposes a high level implementation of electronic voting system, supported by cloud computing architecture and cryptographic technologies, additionally identifying issues that require further research.